2019
DOI: 10.1371/journal.pone.0217224
|View full text |Cite
|
Sign up to set email alerts
|

Concreteness and emotional valence of episodic future thinking (EFT) independently affect the dynamics of intertemporal decisions

Abstract: During intertemporal decisions, the value of future rewards decreases as a function of the delay of its receipt (temporal discounting, TD). Since high discount rates have been associated with a series of problematic behaviours and clinical conditions, current research has focused on possible modulators of TD. Specifically, a reduction of individual discount rates has been shown during episodic future thinking (EFT), wherein time intervals are anchored to personal future events. However, it is not entirely clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 78 publications
12
49
1
1
Order By: Relevance
“…Zhang et al, 2018), while several recent studies demonstrated that negative EFT was associated with a reduction of delay discounting (Bulley et al, 2019;Calluso et al, 2019). Calluso et al (2019) demonstrated that EFT effect was guided by a concreteness effect, and the emotional valence exerted a cumulative effect of the increased farsightedness. In the current study, all the EFT and ERT F I G U R E 2 Mean AUC for EFT and ERT group in both small and large magnitude conditions (error bar represents SE).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Zhang et al, 2018), while several recent studies demonstrated that negative EFT was associated with a reduction of delay discounting (Bulley et al, 2019;Calluso et al, 2019). Calluso et al (2019) demonstrated that EFT effect was guided by a concreteness effect, and the emotional valence exerted a cumulative effect of the increased farsightedness. In the current study, all the EFT and ERT F I G U R E 2 Mean AUC for EFT and ERT group in both small and large magnitude conditions (error bar represents SE).…”
Section: Discussionmentioning
confidence: 99%
“…Another related explanation is that according to the Construal Level Theory (Trope & Liberman, 2000, the distant future events are abstractly represented with high construal level, the EFT may induce farsighted decisions in participants by shifting their time construal from an abstract, high level to a concrete, low level; that is, by representing the future events and rewards more concretely, the participants preferred to choose delayed rewards (Calluso et al, 2019). Given that positive autobiographical memory retrieval also decreased delay discounting (Lempert, Speer, Delgado, & Phelps, 2017), we speculate that simulating distant events (both imagining and remembering) could produce similar shift in time construal and then induce farsighted choice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations